Intensity Loss of ZnO Coated on Fiber Optic - Noor Azie Azura, Mohd Arif; Sahbudin, Shaari; Abang Annuar, Ehsan (Hindawi Publishing, 2023)
Macrobends are optical fiber structures suitable for detecting motion changes. This structure has been developed using single-mode fibers and a combination of single-mode and multimode fibers called hetero-core. In this study, a new macrobending structure was designed and developed by adding a nano-ZnO element to the fiber optic core based on Revolution 4.0. The addition of nanomaterial elements involves an etching process that uses harmful chemicals or high-cost laser technology. Therefore, hetero-core was applied in this study to replace the etching process. The ZnO-coated fiber optics with 10 (ZnO1), 20 (ZnO2), and 30 (ZnO3) times of dip coating were developed using the dip-coating method and characterized using scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. Sensitivity measurement was conducted with glued optical fiber in the form of bending using a tape with a bending dimension of 2.5 cm × 1.5 cm and a wavelength of 1,550 nm. Morphological characterization using SEM proves that nanoparticles are attached to the optical fiber, and the EDX characterization confirms that the nanoparticles are ZnO elements. Optical fiber sensor sensitivity using core sizes 9, 50–9–50, 50–9–50 (ZnO1), 50–9–50 (ZnO2), and 50–9–50 (ZnO3) achieved sensitivity values of 0.91, 1.61, 2.98, 3.34, and 3.51, respectively. This study successfully produced ZnO-coated optical fiber sensors with a hetero-core structure without performing the etching process and successfully increased the sensitivity of the sensors.